2017
DOI: 10.1088/2040-8986/aa608d
|View full text |Cite
|
Sign up to set email alerts
|

Speckle noise reduction in the laser mini-projector by vibrating diffuser

Abstract: We proposed a design for a laser mini-projector with a low speckle contrast value and high contrast ratio that maintains system efficiency. The key design is that two diffusers are located in the two sides of the light tunnel. By vibrating the 30 × 30 diffuser under 100 Hz, the speckle contrast value can be decreased to 2.32% which is invisible to the human eye. Considering the trade-off issue of optical efficiency and speckle noise, the most suitable arrangement with circular diffusers is ‘30 × 30H, 5 × 5. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…It is well known that the measurement conditions have a significant impact on measuring the SCR, thus the measurement conditions used correspond to the human eye perception. In order to ensure an accurate SCR value, the parameters used in this work agree with the previously reported work in [15,17,19,22,26] to measure the SCR in a handheld laser projector such as pico-projector. The pixel size of the CCD camera is 5.2 um×5.2 um with a resolution of 1280×1024 pixels.…”
Section: Speckle Reduction Characterizationsupporting
confidence: 56%
See 2 more Smart Citations
“…It is well known that the measurement conditions have a significant impact on measuring the SCR, thus the measurement conditions used correspond to the human eye perception. In order to ensure an accurate SCR value, the parameters used in this work agree with the previously reported work in [15,17,19,22,26] to measure the SCR in a handheld laser projector such as pico-projector. The pixel size of the CCD camera is 5.2 um×5.2 um with a resolution of 1280×1024 pixels.…”
Section: Speckle Reduction Characterizationsupporting
confidence: 56%
“…It can, therefore, be shown that a minimum SCR ranging from 0.035 to 0.04 can be achieved by employing two green lasers and two-dimensional vibration of lenses. The SCR can be further reduced to be under 4% by using optical diffusers or even a combination of them [17], but this will be on the expense of the optical efficiency of the illumination system [19]. For example, in [22], the minimum SCR achieved was from 2.81% to 4.60% with optical efficiency from 34 to 43% by using pairs of high divergence angle diffusers under vibration'.…”
Section: Optimization Of Operating Frequenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The second diffuser is removed from the Pico LASER projector design used in the speckle testing experiments to make it more compact in size. Two diffusers are used in Type 3 for comparison with previous studies [7,20]. The divergence angles of the circular distribution diffusers are 5 degrees (5X5), 10 degrees (10X10) and 30 degrees (30X30) and the divergence angles of the elliptical distribution diffusers are 5 degrees and 30 degrees (5X30), 10 degrees and 50 degrees (10X50), and 20 degrees and 80 degrees (20X80), described as the angle of the full width at half maximum (FWHM) of the bidirectional transmittance distribution function (BTDF) in the X and Y directions.…”
Section: Speckle Reduction By a Deformable Mirror With Different Diffmentioning
confidence: 99%
“…The coherence can be reduced by using moving, rotating or vibrating optical elements (e.g. diffusers [5][6][7], diffractive optical elements [8], micromirrors [9], multimode fibers or fiber bundles [10]), screen vibration [11], use of broadband lasers [12], multiwavelength illumination (e.g. mode hop of laser diode) [13], etc.…”
Section: Introductionmentioning
confidence: 99%